Investigação soroepidemiológica e molecular de brucelose e leptospirose em núcleos de conservação de gado curraleiro pé duro e pantaneiro - ROMANI, Alana Flávia (2012)
The locally adapted breeds to different Brazilian ecosystems characterized as an alternative to food production, for presenting, among other characteristics, greater resistance to diseases.The main objective of this study was to evaluate the epidemiological situation of brucellosis and leptospirosis in nucleus of in situ conservation of Curraleiro and Pantaneiro bovine breeds in Cerrado and Pantanal biomes by serological and molecular diagnosis of these diseases in the livestock. We analyzed serum of 1,280 Curraleiro and 248 Pantaneiro animals on convenience sampling. We employed microscopic agglutination test, for the diagnosis of leptospirosis and the buffered acidified antigen test (Rose Bengal plate test) for brucellosis and 2-mercaptoethanol test for confirmation. The frequency of brucellosis in Curraleiro was 0.7% for animals and 25% for herds. In Pantaneiros, all animals tested were negative for Brucella abortus. The frequency of anti- Leptospira antibodies was 44.8% in Curraleiro and 51.2% in Pantaneiros, and 100% of the herds of both breeds showed positive animals. The factors associated with leptospirosis were access to wetland, abortions, vaccination against leptospirosis and practice of slaughtering in the propertyfor Curraleiro breed; and sex and age, with the highest risk for females aged between 12 and 24 months for Pantaneiro breed. Serological methods were employed above and polymerase chain reaction (PCR) for detecting infection by Brucella spp. and Leptospira spp. in cattle, to evaluate the concordance of the results of such tests. Brucellosis shows low frequency in Curraleiro cattle and is controlled in Pantaneiro. Leptospirosis was widely disseminated in nucleus of in situ conservation. In both breeds the serovars Hardjo and Wolffi were the most prevalent, which reinforce the function of bovine as a source of infection in the herd. However, the presence of reactions to serovars characteristic of wild animals suggests the involvement of local wildlife in the epidemiology of bovine leptospirosis in these nuclei of in situ conservation. The correlation of results obtained by serology and PCR to identify infection by Brucella spp. and Leptospira spp. was weak, which reinforces the idea that the diagnosis is more reliable when more than one method is employed.